Controlled growth of ZnO nanoflowers on nanowall and nanorod networks via a hydrothermal method. Issue 3 (18th November 2014) - Tang, Jian-Fu; Su, Hsiu-Hsien; Lu, Yang-Ming; Chu, Sheng-Yuan
Abstract : Attempts to produce a network of nanorods and nanowalls on the same substrate at the same time led to the formation of nanoflowers. Abstract : This study developed a hydrothermal method for the growth of three types of zinc oxide (ZnO) nanostructures: nanorods, nanowalls and nanoflowers. The structures are produced at high densities with a high degree of uniformity on Al-coated SiO2 substrates without the need for surfactant. Unlike the random distribution of ZnO nanoflowers reported in previous studies, the proposed method makes it possible to control the distribution of these structures along the grooves created by altering the growth rate of ZnO nanorods and nanowalls. The number of ZnO nanoflowers created in this manner depends on the concentration of solution (HMT: hexamethylenetetramine) and reaction time. Measurements of cathodoluminescence (CL), X-ray diffractometry (XRD), and SEM-EDS confirm that the resulting structures are pure ZnO with good crystallinity. We also investigated the optical properties of these ZnO nanostructures and propose a possible growth mechanism.